2011
DOI: 10.1108/17508611111182368
|View full text |Cite
|
Sign up to set email alerts
|

Social enterprise and social entrepreneurship research and theory

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
84
1
11

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(102 citation statements)
references
References 67 publications
(82 reference statements)
6
84
1
11
Order By: Relevance
“…Previous social entrepreneurship research revolved primarily around its definition and conceptualization (Granados et al 2011;Kraus et al 2014;Sassmannshausen and Volkmann 2016). However, even though there is no consensus yet about the definition of social entrepreneurship (Choi and Majumdar 2014), a definition should logically draw upon entrepreneurial processes that require opportunity exploitation and resource (re)combination processes (Newth and Woods 2014).…”
Section: Social Entrepreneurship and Innovationmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous social entrepreneurship research revolved primarily around its definition and conceptualization (Granados et al 2011;Kraus et al 2014;Sassmannshausen and Volkmann 2016). However, even though there is no consensus yet about the definition of social entrepreneurship (Choi and Majumdar 2014), a definition should logically draw upon entrepreneurial processes that require opportunity exploitation and resource (re)combination processes (Newth and Woods 2014).…”
Section: Social Entrepreneurship and Innovationmentioning
confidence: 99%
“…Previous research focused predominantly on defining, conceptualizing, and describing the phenomenon of social entrepreneurship (Granados et al 2011;Sassmannshausen and Volkmann 2016;Zahra et al 2009). However, even though social entrepreneurs are characterized as innovative individuals (Zahra et al 2009), the actual innovation process is still an understudied theme in social entrepreneurship (Chalmers and Balan-Vnuk 2013).…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest that social entrepreneurship research remains in an embryonic state." Granados et al (2011) and Sassmannshausen and Volkmann (2013) also demonstrated that mostly SE papers with high citations did not have empirical sections and had usually used qualitative approaches. On the other hand, in the realm of SE conceptual papers had been dominant (Hoogendoorn et al 2010).…”
Section: Empirical Definition Of Sementioning
confidence: 99%
“…Although Social Enterprise is becoming an emerging field of interest for both academics and practitioners (Granados et al, 2011), SEs contributors agreed that they remain an underresearched phenomenon (Robinson et al, 2009;Castresana, 2013;Urban, 2015). It is known that SEs are operating in normal market conditions transforming inputs into outputs through production of goods or services (Doherty et al, 2009;Leahy and Villeneuve-Smith, 2009;Villeneuve-Smith, 2011).…”
Section: Social Enterprisesmentioning
confidence: 99%